Geometric patterns windows and doors Masjid Jamek Sultan Abdul Samad Kuala Lumpur / Khalilah Qamaria Eizar Azlan and Wan Nur Rukiah Mohd Arshard - Eizar Azlan, Khalilah Qamaria; Mohd Arshard, Wan Nur Rukiah (2023)
The growth of Islamic visual arts in Malaysia has been strongly influenced by Islamic culture. A few visual arts elements have been produced in accordance with Islamic art guidelines. The mosque's architectural style highlights three characteristics of Islamic art: calligraphy, arabesques, and geometric patterns. There are advantages to everything. The study focuses on the application of Islamic geometric patterns that are visible in the mosques at Masjid Jamek Abdul Samad in Kuala Lumpur. Islamic geometric is used as a mark of identity in the decorative window and door. Observation and case studies are the qualitative methods used in this study to gather data. Every mosque features a minaret, pulpit, and an archway in addition to these three components. The findings showed that the geometric designs of Islamic mosques differ in each state of Malaysia. This is since certain state mosques in Malaysia do not give the mosque's Islamic architectural component a high priority.